Auditing in the Time of Covid-19 and Trends in Auditor Reporting in Romania: A Synthesis and Opportunities for Research - Andrei M. OLARIU (Communications of International Proceedings, 2023)
The goal of the audit process is to gather enough pertinent audit information to allow the auditor to provide an opinion on the financial statements. The final auditor's report is the most obvious means of communication between the auditor and those who will be using the financial statements. This paper aims to summarize the literature on audit reporting, focusing on both uncertainty risk of going concern regarding Romanian companies listed on Bucharest Stock Exchange Market and updating on latest developments in audit reporting. Also, I give a brief overview of the audit opinions that were issued to Romanian listed firms between 2018 and 2021. In order to encourage more study, I concentrate on auditor reports from the most recent time frame (i.e., 2018 to 2021), since previous studies have demonstrated that changes for going concern uncertainty grew after the effects of turbulent times induced in the socio-economic environment, such as the global financial crisis in 2007. Hence, I focus on the years 2018-2021, a period of time that reflects ongoing uncertainty in the Romanian economy (somehow similar to the one experienced in 2007), as a result of the massive repercussions of the Coronavirus outbreak. I therefore see a need for further study to look at the substance and use of the improved auditor's report, building on the studies summarized in this synthesis.
Keywords: audit reporting; going concern; Bucharest Stock Exchange Market; Covid19